2017
DOI: 10.1002/fsn3.552
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional, physicochemical, and functional properties of protein concentrate and isolate of newly‐developed Bambara groundnut (Vigna subterrenea L.) cultivars

Abstract: Bambara groundnut is an indigenous African vegetable grown mainly for human food and animal feed due to its high protein content. Different factors like varieties and origin can influence the chemical composition of Bambara groundnut cultivars. Therefore, the aims of this study are to produce defatted flour and protein concentrate from newly developed Bambara groundnut cultivars [Accessions No: TVSU 5 – Bambara Groundnut White (BGW) and TVSU 146 – Bambara Groundnut Brown (BGB)] and compare their nutritional, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 32 publications
4
23
4
Order By: Relevance
“…The swelling index increase (1.05-1.31) significantly (p≤0.05) as the BGN flour increases within the samples from 0% up to 100%, while no significant difference (p≤0.05) was observed in bulk density (0.62 g ml -1 ) of substituted blend samples of BGN flour from 20%-100%. This result were comparable to 0.56 and 0.62 g ml -1 reported by previous findings (Eltayeb et al, 2011 andAdeleke et al, 2018). The presence of higher proportion of carbohydrate in WF may be responsible for the high BD demonstrated.…”
Section: Functional Propertiessupporting
confidence: 89%
“…The swelling index increase (1.05-1.31) significantly (p≤0.05) as the BGN flour increases within the samples from 0% up to 100%, while no significant difference (p≤0.05) was observed in bulk density (0.62 g ml -1 ) of substituted blend samples of BGN flour from 20%-100%. This result were comparable to 0.56 and 0.62 g ml -1 reported by previous findings (Eltayeb et al, 2011 andAdeleke et al, 2018). The presence of higher proportion of carbohydrate in WF may be responsible for the high BD demonstrated.…”
Section: Functional Propertiessupporting
confidence: 89%
“…Besides, BGPI displays high thermal stability, which is comparable with mung bean, black bean, and soy protein isolates (38,104). Studies reported variable results on the physicochemical properties (water and oil absorption capacities, gelation capacity, and foaming and emulsifying properties) of BGPI (105)(106)(107). The differences in functional properties of BGPI can be explained by several factors, including the amino acid composition (104), extraction method (38), extraction condition (108), and drying condition (109).…”
Section: Bambara Groundnut Protein Isolatementioning
confidence: 99%
“…Bambara groundnuts (Vigna subterranea) were selected for this study, first because they are relied on to provide nutrition to famine prone rural populations, due to their drought-tolerance and high nutrient-density. 15,18 Bambara groundnuts are reported to be a rich source of minerals. A serving of 100 g is calculated to potentially provide more than 50% of the recommended daily allowance of K, Mg and Zn.…”
Section: Introductionmentioning
confidence: 99%